Pengaruh Perilaku (Kompetensi Kepribadian) Guru Pai Terhadap Akhlak Siswa - hidayat, muhamad; Saifullah, Iman; Usman, Asep (Jurnal Pendidikan Agama Islam, 2024)
Teacher personality competency is the ability of a teacher's personality to be solid, stable, mature, wise and dignified, to be a role model for students and to have noble character. Meanwhile, morals are a person's inner state which is driven by the desire to do good in everyday life which is reflected in their words, attitudes and actions. Based on the results of observations made by researchers, it was found that PAI teachers had met the personality competency indicators and were able to apply them optimally. However, on the other hand, it was also found that students' morals did not reflect good morals. Therefore, researchers are motivated to raise this problem in a study entitled: The Influence of PAI Teacher Behavior (Personality Competence) on the Morals of Class VIII MTs Students in Fadilatul Huda. The aim of this research is to find out how much influence teacher behavior (personality competence) has on student morals specifically at MTs Fadilatul Huda class VIII with a sample of 23 people. This research was carried out by distributing questionnaires, observations, interviews and documentation. The method used in this research is a descriptive quantitative method where the research process uses statistics to analyze data by describing or describing what has been collected as it is without intending to draw conclusions that apply generally. Based on the results of data analysis, it can be concluded that the student response to variable (X) shows a percentage of 84.73% in the very good category and the student response to variable (Y) shows a percentage of 87.15% in the very good category. So it can be concluded that "There is an influence between the personality competence of PAI teachers on student morals" with a percentage value of 45.8% and influence from outside of 54.2%.